Electrochemical Scanning Tunneling Microscopy as a Tool for the Detection of Active Electrocatalytic Sites - Schmidt, Thorsten O.; Haid, Richard W.; Gubanova, Elena L.; Kluge, Regina M.; Bandarenka, Aliaksandr S. (Topics in catalysis, 2023)
To advance meaningful guidelines in the design of electrocatalytically active catalysts, a knowledge of the nature of active sites is the starting point. However, multiple factors such as material composition, site coordination, electrolyte effects, the support material, surface strain, and others influence catalytic behavior. Therefore, the identification of active sites can be complex. A substantial contributor can be in-situ experiments, which are able to identify active centers in a specific system while the reaction takes place. An example of such a technique is electrochemical scanning tunneling microscopy (EC-STM), which relates locally confined noise features to local electrocatalytic activity. In this work, we spotlight recent achievements of this technique with respect to palladium (Pd) surfaces for the hydrogen reduction reaction, where strain due to hydride formation comes into play in addition to surface coordination. Secondly, we demonstrate the high resolution of the technique on graphite-based surfaces. Here, edge sites are particularly active. Thus, with the EC-STM technique, we take strain effects (like on Pd) or effects of coordination (like on carbon) into account. Therefore, we can determine active sites with great accuracy under reaction conditions.